Pulsed Radiofrequency for Post-Covid Occipital Neuralgia: An Effective Therapeutic Proposal - Case Report - Vale, Caroline Calheiros do; Cavalcanti, João Victor Cinicio; Guimarães, Brunna Gerlany Freire; Caetano, Maria Eduarda Pinto; Piscoya, Guilherme de Vasconcellos; Gemir, Júlia Lins; Silva, Gisele Carvalho; Alencar Neto, Joaquim Fechine de; Ferreira Neto, Otávio da Cunha; Marques, Luís Felipe Ferreira; et al. (Headache Medicine, 2022)
With the SARS-CoV-2 pandemic and the increased number of cases reported in the literature of post-Covid syndromes, and clinical conditions of rheumatic and cardiovascular diseases, neurological disorders have also been reported, with the description of cases of reduced memory and cerebrovascular complications post-Covid-19 virus infection. Thus, in addition to these conditions, neuropathic pain secondary to cases of novel coronavirus infection have been seen in the literature and have raised questions about the pathophysiology arising from this situation, prognostic factors, and best indications for treatment. Among the neuropathic pain reported, occipital neuralgia is one of the complications faced, characterized by a burning and paroxysmal pain of variable duration. One of the possible treatments for this condition is the use of pulsed radiofrequency on the affected nerves in cases refractory to optimized clinical treatment, being an effective measure for reducing symptoms and improving quality of life.